2015
DOI: 10.1002/bit.25605
|View full text |Cite
|
Sign up to set email alerts
|

The role of electron donors generated from UV photolysis for accelerating pyridine biodegradation

Abstract: Employing an internal circulation baffled biofilm reactor (ICBBR), we evaluated the mechanisms by which photolysis accelerated the biodegradation and mineralization of pyridine (C5 H5 N), a nitrogen-containing heterocyclic compound. We tested the hypothesis that pyridine oxidation is accelerated because a key photolysis intermediate, succinate, is as electron donor that promotes the initial mono-oxygenation of pyridine. Experimentally, longer photolysis time generated more electron-donor products (succinate), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Recently, researchers have been able to develop combined photocatalytic–biological systems to enhance contaminant removal efficiency . These strategies have been successfully demonstrated by fast biodegradation rates of organic pollutants such as trichlorophenols and dyes. , Considering the oxidative stress of photocatalysts (especially the PNPs) to organisms, intimately coupled photobiocatalytic processes need complicated reactor configurations to protect microorganisms from being attacked or killed by PNPs or materials with lower toxicity to microorganisms. Periphytic biofilm, as a model multispecies microbial aggregate, exhibits constant adaptation of its population fitness to protect microorganisms against PNP stress. This study demonstrated that periphytic biofilm possesses the potential to combine with photocatalysis as periphytic biofilm can maintain its growth in the presence of PNPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, researchers have been able to develop combined photocatalytic–biological systems to enhance contaminant removal efficiency . These strategies have been successfully demonstrated by fast biodegradation rates of organic pollutants such as trichlorophenols and dyes. , Considering the oxidative stress of photocatalysts (especially the PNPs) to organisms, intimately coupled photobiocatalytic processes need complicated reactor configurations to protect microorganisms from being attacked or killed by PNPs or materials with lower toxicity to microorganisms. Periphytic biofilm, as a model multispecies microbial aggregate, exhibits constant adaptation of its population fitness to protect microorganisms against PNP stress. This study demonstrated that periphytic biofilm possesses the potential to combine with photocatalysis as periphytic biofilm can maintain its growth in the presence of PNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also exploit strategies to combine PNP based technology with biological processes (i.e., intimately coupled photobiocatalysis) to improve contaminant removal efficiency . However, the biological compatibility of PNPs must be taken into consideration to avoid microorganisms being attacked or killed. CdS, TiO 2 , and Fe 2 O 3 PNPs have shown great application potential in combination with various biological processes, , such as ammonia synthesis from nitrogen, removal of organic pollutants in wastewater, and microbial photoelectrochemical system . Due to large-scale uses, it is necessary to investigate their potential environmental impacts and possible effects on biological systems under sunlight irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to consider that the photohole produced by CdS NPs under illumination could cause oxidative stress or membrane destruction of microbial cells (Li et al, 2013;Tang et al, 2015). To avoid cell damage from photohole-induced stress, the biocompatibility of CdS NPs in mixed cultures must be considered.…”
Section: Physiological Response To Stimulation By Illuminated Cds Npsmentioning
confidence: 99%
“…One source can be carboxylic acids formed during photolysis of nitrogen containing heterocyclic compounds, as has been shown for pyridine. 26,31 Acceleration of steps A and B ought to speed up all the downstream steps, leading to faster mineralization of quinoline.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Steps A and B should be accelerated if an intracellular electron donor (i.e., 2H) is provided from sources other than the steps that mineralize 2,3-dihydroxyphenyl propionic acid. One source can be carboxylic acids formed during photolysis of nitrogen containing heterocyclic compounds, as has been shown for pyridine. , Acceleration of steps A and B ought to speed up all the downstream steps, leading to faster mineralization of quinoline.…”
Section: Introductionmentioning
confidence: 99%